Development of Android-Based Interactive Learning Media Using iSpring Suite Application - Ika Parma Dewi; Habi Akbar; Nizwadi Jalinus; Waskito Waskito; Dedy Irfan (Jurnal Teknologi Informasi dan Pendidikan, 2021)
This study aims to determine the results of the validity and practicality of learning media applications made using the Ispring Suite application. The methodology adopted is Research and Development (R&D) with a 4-D model. The 4-D development model has steps, namely Definition, Design, Development, and Deployment, but in this study it was adopted to the 3rd stage, namely Development due to limited manpower and time. The validity test was carried out by 4 people, namely 2 media experts and 2 material experts. The total validation results of media experts are 94% with very valid categories. The result of material expert validation is 93% with a very valid category. The practicality test was carried out to 9 students of class X TAV SMKN 1 Tanjung Raya. The results of the practicality test assessment for students are 91% in the very practical category. Based on the results of the assessment, it can be concluded that the android-based learning media application using the resulting Ispring Suite application is valid and practical to be used by teachers and students.